A time in motion study of impact of robotics on medication supply in an Australian hospital pharmacy. (21st April 2021) - Hogan, Jane M.; Grant, Gary; Kelly, Fiona S.; O'Hare, Jennie R.
Abstract: Background: Pharmacy robotics have been implemented globally to create medication management efficiencies. However, translation to the Australian public hospital environment has not been evaluated. Aim: To evaluate the impact of introducing robotics in an Australian public hospital on pharmacy imprest and dispensary tasks. Method: A single‐centred, prospective, longitudinal time in motion study was conducted in an Australian tertiary public hospital using mixed methods during robot implementation (phase 1, May 2016) and 15 months later (phase 2, August 2017). Time‐stamped video footage of dispensary activities was collected, observed and analysed; Fitbit Zip ® anonymously tracked pharmacy assistant movement. Dispensing software (iPharmacy ® ) provided the location of stocked medication and electronic tracking databases provided imprest turnaround times (ethics approval: HREC/16/QGC/66, HREC/17/QGC/18). Results: Medication stored in the robot was limited to 46% ( n = 20 771 full packs) of total pharmacy holdings ( n = 45 437 full packs). At baseline, 774 orders were received in the dispensary over five days increasing by 13% to 887 in phase 2 (p < 0.01). Dispensary workload increased, staff levels remained constant and movement was reduced. However, there were no significant changes to dispensing rates and turnaround times. Conclusion: Pharmacy robotics has the potential to absorb increased workload and reduce staff movement in the dispensary when staffing levels remain constant. However, turnaround times alone are too simplistic as a sole measure of benefits of robotics in Australian public hospital pharmacy.